2014
DOI: 10.1371/journal.pone.0106915
|View full text |Cite
|
Sign up to set email alerts
|

Probing Cellular Mechanoadaptation Using Cell-Substrate De-Adhesion Dynamics: Experiments and Model

Abstract: Physical properties of the extracellular matrix (ECM) are known to regulate cellular processes ranging from spreading to differentiation, with alterations in cell phenotype closely associated with changes in physical properties of cells themselves. When plated on substrates of varying stiffness, fibroblasts have been shown to exhibit stiffness matching property, wherein cell cortical stiffness increases in proportion to substrate stiffness up to 5 kPa, and subsequently saturates. Similar mechanoadaptation resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…4C-E). To further test how MUC1 levels influence adhesion, trypsin de-adhesion assay 28,35 was performed wherein spread cells were incubated with warm trypsin and their detachment kinetics tracked for the duration cells rounded up but remained attached to their substrates (Figs 4F, G). Once again, the de-adhesion time, i.e., the time for cells to round up scaled inversely with MUC1 levels with fastest de-adhesion observed in MUC1-High cells, and neuraminidase treatment abolishing the MUC1-dependent behavior (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4C-E). To further test how MUC1 levels influence adhesion, trypsin de-adhesion assay 28,35 was performed wherein spread cells were incubated with warm trypsin and their detachment kinetics tracked for the duration cells rounded up but remained attached to their substrates (Figs 4F, G). Once again, the de-adhesion time, i.e., the time for cells to round up scaled inversely with MUC1 levels with fastest de-adhesion observed in MUC1-High cells, and neuraminidase treatment abolishing the MUC1-dependent behavior (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…De-adhesion assay was performed using protocol described elsewhere 27,28 . Briefly, cells grown on collagen/E-selectin coated dishes for 24 hrs were washed with PBS and incubated with warm (37°C) trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…Stability of cell shape is determined by a force balance between the actomyosin cytoskeleton which exerts inward directed contractile force and focal adhesions which resist these forces. We had earlier shown that this balance can be probed using trypsin-induced de-adhesion wherein time kinetics of cell rounding is followed upon incubation of adherent cells with warm trypsin [36,[41][42][43]. To test how tensional homeostasis is achieved on GelMA gels, trypsin de-adhesion assay was performed (figure 3(A)).…”
Section: Adhesivity Dictates Tensional Homeostasis On Gelma Gelsmentioning
confidence: 99%
“…Directional anisotropy and the degree of anisotropy changes over time and spatially which means that the parameters (κ, σ and γ) have a certain relationship with the growth time and space of pseudopod (i.e. the parameters (κ, σ and γ) are functions of time and space) [50]. Therefore, the resistance energy and all the variables presented (κ, σ and γ) as a function of space and time, and the resistance energy in equation ( 12) can be written as:…”
Section: Incorporate Time Course Dynamics and Stochastic Effects On P...mentioning
confidence: 99%